Proceedings of the 6th Asia-Pacific Bioinformatics Conference 2007
DOI: 10.1142/9781848161092_0012
|View full text |Cite
|
Sign up to set email alerts
|

A MEMORY EFFICIENT ALGORITHM FOR STRUCTURAL ALIGNMENT OF RNAs WITH EMBEDDED SIMPLE PSEUDOKNOTS

Abstract: In this paper, we consider the problem of structural alignment of a target RNA sequence of length n and a query RNA sequence of length m with known secondary structure that may contain embedded simple pseduoknots. The best known algorithm for solving this problem (Dost et al. [13]) runs in O(mn4) time with space complexity of O(mn3), which requires too much memory making it infeasible for comparing ncRNAs (non-coding RNAs) with length several hundreds or more. We propose a memory efficient algorithm to solve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…While generally poorly studied at the early disease stages, it appears that as the disease progresses and requires surgical intervention, almost 50 percent of preoperative osteoarthritis surgical cases may be expected to exhibit anxiety symptoms as observed by Jones et al [19]. While this high number of anxious cases may have been attributable in part to the selfreport mode of estimating anxiety as normal or abnormal, Wong et al [20] as well as Castano et al [21], Stubbs et al [5] and Guglielmo et al [22] all reported the presence of anxiety to be of the order of 20 percent or higher in various osteoarthritis or arthritis samples when this has been assessed.…”
Section: Research-based Observationsmentioning
confidence: 98%
“…While generally poorly studied at the early disease stages, it appears that as the disease progresses and requires surgical intervention, almost 50 percent of preoperative osteoarthritis surgical cases may be expected to exhibit anxiety symptoms as observed by Jones et al [19]. While this high number of anxious cases may have been attributable in part to the selfreport mode of estimating anxiety as normal or abnormal, Wong et al [20] as well as Castano et al [21], Stubbs et al [5] and Guglielmo et al [22] all reported the presence of anxiety to be of the order of 20 percent or higher in various osteoarthritis or arthritis samples when this has been assessed.…”
Section: Research-based Observationsmentioning
confidence: 98%
“…RNA structural alignment, also known as RNA sequence-structure alignment, is the challenging area of bioinformatics, which becomes more challenging and advantageous if the pseudoknots are also considered in the structure. The literature available on pseudoknotted structural alignment of RNA includes simulated annealing [1]; dynamic programming [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]; genetic algorithm [17][18][19]; integer linear programming [20][21][22][23]; graph approach [24][25][26][27]; tree construction [28][29][30][31]; stochastic sampling [32]; Markov chain Monte Carlo [33] and formal grammar [34][35][36].…”
Section: Introductionmentioning
confidence: 99%